Efektivitas Metode Jigsaw Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Fiqih - Muhammad Ilham Khalid Al-Faraby; Imas Siti Fuziah (Ta'lim: The Islamic Religious Educational Journal, 2025)
This research is motivated by the low learning outcomes of students in Fiqh, caused by the frequent teacher-centered lecture-based learning, which tends to make students passive. Therefore, learning that encourages active student participation is needed to improve learning outcomes in accordance with the school's minimum completion criteria. Based on the above issues, the author formulated the following problem: "Is the Jigsaw Method Effective on Student Learning Outcomes in Fiqh for Grade XI Social Studies at MA Darul Falah Cijati in the 2024/2025 Academic Year?" This study aims to determine the effectiveness of the Jigsaw Method on student learning outcomes in Fiqh for Grade XI Social Studies at MA Darul Falah Cijati. This research was conducted at MA Darul Falah Cijati, with all 24 students in grade XI IPS participating as subjects. Jigsaw is defined as a structured group work strategy based on cooperation and responsibility. This strategy ensures that each student assumes significant responsibility within the group. This research used the Classroom Action Research (CAR) method, consisting of two cycles, each encompassing planning, implementation, observation, and reflection. The cycles were terminated when the success indicator, i.e., all students had achieved the school-set learning achievement standard for Fiqh (Islamic jurisprudence) for grade XI IPS, reached 75. The results showed an improvement in students' Fiqh learning outcomes in each cycle. This improvement was demonstrated by an average N-Gain of 44% in cycle I, which increased to 78% in cycle II. 54.17% of students achieved learning achievement in cycle I, and all students achieved learning achievement in cycle II due to improvements in the implementation of the Jigsaw method after evaluating the learning process and learning outcomes. Observations of the learning process indicate that implementing the Jigsaw method in Fiqh (Islamic jurisprudence) makes students enjoy learning. Students become more active, and their enthusiasm and motivation for learning increase. It can be concluded that learning using the Jigsaw method is effective and can improve Fiqh learning outcomes.